REFLECTION OF SIRI VALUES IN WOMEN'S PARTICIPATION: CULTURAL ANALYSIS AND DECISION MAKING IN THE SOUTH SULAWESI DEVELOPMENT PLANNING FORUM (Universitas Islam Negeri Alauddin Makassar, 2026)
Women's participation in the Development Planning Consultation Forum (Musrenbang) is an important indicator in realizing inclusive and equitable development. However, the reality on the ground shows that women's involvement is often not optimal, especially in South Sulawesi, which has the cultural value of Siri' as a guideline for community behavior. This study aims to understand how the cultural value of Siri' influences women's participation in the development planning and decision-making process through the Musrenbang forum in South Sulawesi. This study uses a qualitative method with a socio-cultural approach through literature research reinforced with empirical data. Data collection was conducted through a documentation study of lontara manuscripts, historical documents, Bugis-Makassar cultural literature, as well as analysis of official documents from the South Sulawesi Provincial Government, data from the Central Statistics Agency, reports from the Culture and Tourism Office, and the results of a study by the Regional Research and Development Agency. Data analysis was conducted descriptively and interpretively using content analysis techniques and a hermeneutic approach. The results of the study show that the value of Siri' has an ambivalent influence on women's participation in Musrenbang. On the one hand, Siri' functions as an internal force that encourages women to maintain their self-respect, dare to voice the interests of the community, and fight for fair decisions. On the other hand, cultural constructs that position women as symbols of family honor, coupled with male dominance and power imbalances, limit women's space for expression, resulting in participation that is often formal and not yet substantive. This study emphasizes the importance of positively and contextually internalizing Siri' values in regional development planning to strengthen women's participation that is fair and in harmony with local culture without neglecting the principle of gender equality